ANALISA PENJADWALAN PROYEK DENGAN METODE PERT DAN CPM PADA PEMBANGUNAN GEDUNG HOTEL DI SIDOARJO - Moch Syamsul Maarif (Universitas Muhammadiyah Surabaya, 2022)
The probability of the project being completed on time or according to plan with PERT and CPM methods with Microsoft Project Application is 66%. From the distribution of questionnaires to 26 respondents, it can be concluded that the 3 main factors causing delays in the hotel building project in Sidoarjo, project delays are due to technical factors with a preset value of 87.85%, project delays due to financial factors with a preset value of 77.31%, project delays due to labor and equipment factors with a preset value of 71.03%.